Pertanggungjawaban Pidana Terhadap Perusahaan yang Lalai Mendaftarkan Pekerjanya Sebagai Peserta BPJS Ketenagakerjaan - Indrawati Indrawati; Tumiar Rohana Simanjuntak (Jurnal Cakrawala Hukum, 2019)
This study discusses criminal liability towards companies that fail to register their workers as participating BPJS workers. Social security is very important for all Indonesian workers to have because socioeconomic risks can occur to anyone, anywhere and to anyone. The type of legal research used in this study is normative research. Results and discussion of research conducted where PT. This True Farmer Initiative has made a mistake in the form of negligence or negligence from the company that does not pay BPJS Employment contributions to workers and there are some workers who are not registered as BPJS Employment participants. This has been received by a court ruling punishing the company which resulted in the rights of the workers who could not be fulfilled. Seeing the decision that has been determined by the judge there is no criminal sentence, the judge’s decision does not provide a deterrent effect on the company. The provisions of the BPJS Employment Act currently added the application of imprisonment sanctions, so that in the future it can provide a deterrent effect on companies that fail to register their workers as BPJS Employment participants.How to cite item: Indrawati, I., Simanjuntak, T. (2019). Pertanggungjawaban Pidana Terhadap Perusahaan yang Lalai Mendaftarkan Pekerjanya Sebagai Peserta BPJS Ketenagakerjaan. Jurnal Cakrawala Hukum, 10(1), 50-57. doi:https://doi.org/10.26905/idjch.v10i1.3180